2020
DOI: 10.1038/s41598-020-66142-2
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation in tooth regeneration of Ambystoma mexicanum

Abstract: the presence of nerves is an important factor in successful organ regeneration in amphibians. the Mexican salamander, Ambystoma mexicanum, is able to regenerate limbs, tail, and gills when nerves are present. However, the nerve-dependency of tooth regeneration has not been evaluated. Here, we reevaluated tooth regeneration processes in axolotls using a three-dimensional reconstitution method called coMBi and found that tooth regeneration is nerve-dependent although the dentary bone is independent of nerve pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Tooth regeneration was investigated as an additional phenomenon besides mandibular regeneration. The trigeminal nerves provide axons to axolotl teeth and express Fgf genes in addition to the DRG neurons and the spinal cord (Makanae et al, 2020). Denervation of axons from the trigeminal ganglia resulted in a severe delay in tooth regeneration.…”
Section: Regeneration Induction In Other Organsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tooth regeneration was investigated as an additional phenomenon besides mandibular regeneration. The trigeminal nerves provide axons to axolotl teeth and express Fgf genes in addition to the DRG neurons and the spinal cord (Makanae et al, 2020). Denervation of axons from the trigeminal ganglia resulted in a severe delay in tooth regeneration.…”
Section: Regeneration Induction In Other Organsmentioning
confidence: 99%
“…Ectopic expression of Fgf2, Fgf8, and Bmp7 can reverse the delay in tooth regeneration that is caused by denervation. However, denervation could not completely prevent tooth regeneration (Makanae et al, 2020). Denervation procedures in the axolotl regeneration study are usually accompanied by axon regrowth at the end.…”
Section: Regeneration Induction In Other Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation can add molecular data to the 3D morphological data, although the molecular data are limited to 2D distribution. To date, the CoMBI-C system has been used in various research fields, such as 3D analysis of primordia of beetle horn 16 , 3D distribution analysis of myelinated fibers of human facial nerves 17 , 3D morphological analysis of polycystic kidney of knockout mice 18 , and 3D visualization of regenerating bones and cartilage of the axolotl jaw 19 . Through these collaborative studies and ongoing collaborations, we found that users of the conventional CoMBI-C system desired compatibility with not only frozen specimens but also paraffin-embedded specimens.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the development of cranial foramina, or passageways of the skull, has been proposed to rely on sensory nerves and vasculature to restrict ossification to discrete domains (Akbareian et al, 2015). Additionally, damage to bony structures results in mis-patterned, incomplete repair when the tissue is denervated, as observed in deer antlers (Suttie and Fennessy, 1985), mouse femurs (Chen et al, 2019), and axolotl teeth (Makanae et al, 2020). In humans with congenital insensitivity to pain, a condition arising from an incomplete peripheral nervous system, patients experience significant musculoskeletal disorders, including repeated fractures (Bar-On et al, 2002;Mifsud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%